1998
DOI: 10.1523/jneurosci.18-06-02009.1998
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1Receptors Facilitate GABAASynaptic Currents in the Rat Substantia Nigra Pars Reticulata

Abstract: GABA neurons in the substantia nigra pars reticulata receive input from GABAergic fibers originating in the forebrain. The role of dopaminergic D1 receptors located on these fibers was investigated using tight-seal whole-cell recordings from visually identified pars reticulata neurons of rat substantia nigra slices. Nondopaminergic pars reticulata neurons were characterized by their electrophysiological properties. Postsynaptic currents evoked by minimal stimulation in the presence of ionotropic glutamate rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
133
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 46 publications
15
133
5
Order By: Relevance
“…With this method, a presynaptic D 2 -mediated modulation similar to that shown on the striatopallidal pathway (Cooper and Stanford, 2001;Mengual and Pickel, 2002) or in the cholinergic or fastspiking (FS) interneurons (Pisani et al, 2000;Momiyama and Koga, 2001;Centonze et al, 2003) was shown. Similarly, a presynaptic modulation by D 1 receptor agonists as that reported in the striatonigral pathway (Floran et al, 1990(Floran et al, , 1997Cameron and Williams, 1993;Radnikow and Misgeld, 1998) was also shown, despite postsynaptic dopaminergic actions (Pacheco-Cano et al, 1996) on the subthreshold inward rectification Nisenbaum and Wilson, 1995;Mermelstein et al, 1998;Farries and Perkel, 2000) that shunts inhibitory inputs (Fitzpatrick et al, 2001).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…With this method, a presynaptic D 2 -mediated modulation similar to that shown on the striatopallidal pathway (Cooper and Stanford, 2001;Mengual and Pickel, 2002) or in the cholinergic or fastspiking (FS) interneurons (Pisani et al, 2000;Momiyama and Koga, 2001;Centonze et al, 2003) was shown. Similarly, a presynaptic modulation by D 1 receptor agonists as that reported in the striatonigral pathway (Floran et al, 1990(Floran et al, , 1997Cameron and Williams, 1993;Radnikow and Misgeld, 1998) was also shown, despite postsynaptic dopaminergic actions (Pacheco-Cano et al, 1996) on the subthreshold inward rectification Nisenbaum and Wilson, 1995;Mermelstein et al, 1998;Farries and Perkel, 2000) that shunts inhibitory inputs (Fitzpatrick et al, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…If that were true, a consistent dopaminergic modulation should be seen, which was the case, resulting in the initial description of this modulation. In addition, neostriatal projection neurons express D 1 or D 2 receptors (Surmeier et al, 1993;Hernandez-Lopez et al, 1997, 2000Aizman et al, 2000), and consistent presynaptic actions as the result of the activation of these receptors have been reported at the target nuclei (Floran et al, 1990(Floran et al, , 1997Cameron and Williams, 1993;Radnikow and Misgeld, 1998;Cooper and Stanford, 2001). Moreover, D 1 postsynaptic actions are facilitatory (Hernandez-Lopez et al, 1997), whereas D 2 postsynaptic actions depress firing (Hernandez-Lopez et al, 2000) in spiny neurons.…”
Section: Ipscs From Axon Collateralsmentioning
confidence: 64%
See 3 more Smart Citations